The hidden mirror: Sexual and gender minorities in agricultural research - O'Keefe, Geoffrey (Australian Centre for International Agricultural Research, 2019)
Presented by Geoffrey O'Keefe (Australian Centre for International Agricultural Research), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.